2018
DOI: 10.1080/24750263.2018.1498927
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive expression dynamics and comparative toxicological perspective of beta estrogen receptor gene in the male wall lizard, Podarcis sicula Rafinesque, 1810 (Chordata: Reptilia)

Abstract: Over the last few decades, due to its relevant function in male reproduction assessment, important molecular achievements have been made in the molecular characterization of estrogen receptor genes in various species. Our work focuses on a male seasonal breeder, the bioindicator Podarcis sicula, because of its peculiar gonadal anatomy, similar to that of humans. Based on the cloned lizard's gene sequence fragment of estrogen receptor beta, esr2 (GenBank JN705543.1), we found DNA binding domain identity of 99% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…Drug exposure in the maturation stage during the hottest time period, with the aim of mimicking emerging estrogenic pollutants in the environment, showed a slowing of spermatogenesis processes into seminiferous tubules, a reduced lumen, and a depletion of sperm quantity. Testicular changes and spermatogenesis arrest at secondary spermatocyte levels were observed, highlighting a reorganization of testicular structure impacting male fertility [98].…”
Section: Reptiliamentioning
confidence: 99%
See 2 more Smart Citations
“…Drug exposure in the maturation stage during the hottest time period, with the aim of mimicking emerging estrogenic pollutants in the environment, showed a slowing of spermatogenesis processes into seminiferous tubules, a reduced lumen, and a depletion of sperm quantity. Testicular changes and spermatogenesis arrest at secondary spermatocyte levels were observed, highlighting a reorganization of testicular structure impacting male fertility [98].…”
Section: Reptiliamentioning
confidence: 99%
“…Analyses on Reptilia Squamata, such as on the ruin Lacertidae, Podarcis sicula, showed how combined factors, as well as high temperature and the activity of xenobiotics released into the environment, affect their physiology [5,98]. Specifically, the antioxidant defense activity by glutathione peroxidase 4 (gpx4), which was observed under steroid control [131,132], showed that over-expression in the testis is followed by an opposite trend in relation to the feedback of the brain (hypothalamus-pituitary)-gonad axis, indicating steroid control [5,85].…”
Section: Reptiliamentioning
confidence: 99%
See 1 more Smart Citation
“…In the brain adaptation the steroids, for example, play an important role because these hormones are secreted in response to environmental signals that are processed by the nervous system and then act back on specific areas to modify their function (reviewed in Guerriero, ). Because changes in the development, adult life, and degree of environmental pollution can alter genomic activity, steroid hormones as well as steroid receptors, and antioxidants under steroid control give us unique insight into the role of the genome in the control of brain reproductive and nonreproductive function (Guerriero, Di Giaimo, et al, ; Guerriero, Roselli, & Ciarcia, ; Guerriero, Trocchia, Abdel‐Gawad, & Ciarcia, ). Selenoproteins are part of the antioxidant network, which consists of nonenzymatic antioxidant compounds and a large number of redox‐active enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…They also enter humans through the food chain [2]. For an environmentally friendly assessment of contamination, tissues such as blood plasma of fish [3], frog skin by biopsy [4], lizard single gonadectomy [5], bird fece [6] and feather [7] may be useful. Among invertebrates, the aquatic insects are key biotransporters of contaminants between aquatic and terrestrial ecosystems [8,9].…”
Section: Introductionmentioning
confidence: 99%